Peranan Biaya Advertising dan Biaya Sales Promotion dalam Meningkatkan Nilai Penjualan pada PT. Gunung Agung di Bandar Lampung - Zuriana - (Jurnal Bisnis Darmajaya, 2015)
CV Gunung Agung established since 1990 is a company which is a branch of PT. Great Mountain Center. As a branch company, product and price has been arranged so that the uniformity of the product and the price is no different in different regions. During the establishment of this company until this year the company has not been able to achieve the sales target has been set from the center. While promotional activities in the form of advertising and sales promotion to achieve the sales target continues to be maximized.Thus, the problem is how the role of the cost of advertising and sales promotion expenses to the value it sold PT. Gunung Agung Lampung branch.The hypothesis is the cost of advertising and sales promotion costs greatly affect the sales of the Supreme PT.Gunung Lampung branch.Setelh testing, it turns out variabeladvertising effect on sales. Figures advertising costs variable coefficient β1 = 14.9830 indicates that every increment of Rp. 1 (the rupiah) would add to the cost of advertising sales of Rp. 14.9830. Variable coefficient value of sales promotion costs would lead to increase in the sales value of Rp. 7.1766.In terms of the contribution of each variable is seen that the administrative costs contributed terhadapnilai greater sales when compared to the cost of sales promotion. But in terms of the relationship between variables is seen that the variable cost of sales promotion more closely (94.56%) when compared with the cost of advertising (90.61%).While in terms of contribution to sales variable, together the two variables provide a contribution of 90.37% while the rest of 9.67 was obtained from other variables, such as personal selling or other marketing variables.Keywords: Variable, Advertising, Sales Promotion, Sales